2016
DOI: 10.1080/10428194.2016.1180682
|View full text |Cite
|
Sign up to set email alerts
|

IKZF1 alterations and expression of CRLF2 predict prognosis in adult Chinese patients with B-cell precursor acute lymphoblastic leukemia

Abstract: Acute Lymphoblastic Leukemia (ALL) is a common hematological malignancy in children, with a prognosis much worse in adults. The molecular characterization of ALL and its correlated prognostic significance are largely unknown. In this study, we analyzed the frequency of IKZF1 deletions, IK6 isoform, and CRLF2 overexpression in 118 Chinese adult B-cell precursor ALL (B-ALL) patients to explore their associations with clinical prognosis. Our data showed that IKZF1 deletions and IK6 isoform were highly detected in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 21 publications
2
6
0
Order By: Relevance
“…For example, IKZF1 deletion, a hallmark of high-risk pediatric ALL, is related to poor prognosis in adult ALL ( 4 10 ). This phenomenon was consistent with our previous study, wherein IKZF1 deletion was associated with poor survival in adult B-ALL patients ( 11 , 12 ).…”
Section: Introductionsupporting
confidence: 94%
“…For example, IKZF1 deletion, a hallmark of high-risk pediatric ALL, is related to poor prognosis in adult ALL ( 4 10 ). This phenomenon was consistent with our previous study, wherein IKZF1 deletion was associated with poor survival in adult B-ALL patients ( 11 , 12 ).…”
Section: Introductionsupporting
confidence: 94%
“…As mentioned earlier, patients with IKZF1 gene deletions did not exhibit a poor prognosis in the present study, which may be attributed to the small sample size and short follow-up duration. In addition, it was revealed that MLPA was less sensitive than PCR in analyzing the IKZF1 gene deletions, which may result in an increased number of false negative cases and may influence the prognostic significance of such observations (8).…”
Section: Discussionmentioning
confidence: 99%
“…51104; Qiagen GmbH, Hilden, Germany) was used for DNA extraction, according to the manufacturer's protocols. TRIzol™ (Life Technologies; Thermo Fisher Scientific, Inc., Waltham, MA, USA) was used to extract RNA, RNA was also extracted from the MNCs of 50 patients (MNCs <10 6 , as dictated by the TRIzol protocol) and was synthesized into cDNA, as previously described (8). Nested reverse transcription polymerase chain reaction (RT-PCR) was performed, as previously described (PCR Master mix; Takara Biotechnology Co., Ltd., Dalian, China) (8).…”
Section: Methodsmentioning
confidence: 99%
“…Some studies have shown an association between CRLF2 overexpression and adverse prognosis, whereas others have demonstrated a correlation between P2RY8 ‐ CRLF2 and an inferior outcome. The prognostic value of CRLF2 overexpression and P2RY8 ‐ CRLF2 in B‐ALL with different risk features, particularly intermediate‐ and low‐risk B‐ALL, has not yet been well established 14–16 . Furthermore, it has been reported that the abnormal expression of CRLF2 is not suggestive of poor prognosis in B‐ALL 17 .…”
Section: Discussionmentioning
confidence: 99%